Caractéristiques des sites de mise bas de l'orignal ( Alces alces ) - Chekchak, Tarik; Courtois, Réhaume; Ouellet, Jean-Pierre; Breton, Laurier; St-Onge, Sylvain (Canadian Journal of Zoology, 1998)
The movements of female moose, 14 in 1995 and 20 in 1996, were recorded by radio-tracking to examine the characteristics of calving sites in the centre of Quebec. Females were spotted by helicopter every 3 or 4 days mean = 3,5 ± 0,4; n = 15) between mid-May and early June (1995: May 17 - June 9; 1996: May 21 - June 6) so that the exact dates and sites of calving could be determined. Topography and vegetation at the sites were determined using topographic maps and terrestrial surveys and were compared with control sites chosen randomly within the home range of each female. Twenty-six calving sites were identified, 10 in 1995 and 16 in 1996. Calving sites were situated seven times more often at the top of hills (69%; n = 26) than control sites (10%). They were also situated more often (88%) on hills with less than 10% slopes than control sites (52%). Finally, distance to the nearest river was greater for calving sites mean = 543 m) than for control sites mean = 339 m). Canopy and food, altitude, distance to a road or a water source, drainage, and orientation did not differ between calving sites and control sites. Although this is not a formal test, the observed characteristics of calving sites support the hypothesis that calving females choose sites where the risks of fawn predation are lowest. As females do not repeatedly use the same calving sites and as the physical characteristics of the sites and nature of the forest at the sites are not limiting, we do not see any reason why moose calving sites should be submitted to particular protection or management measures.